1993
DOI: 10.1128/mcb.13.11.6789
|View full text |Cite
|
Sign up to set email alerts
|

The HRIGRXXR region of the DEAD box RNA helicase eukaryotic translation initiation factor 4A is required for RNA binding and ATP hydrolysis.

Abstract: eIF-4A is a eukaryotic translation initiation factor that is required for mRNA binding to ribosomes. It exhibits single-stranded RNA-dependent ATPase activity, and in combination with a second initiation factor, eEF-4B, it exhibits duplex RNA helicase activity. eEF-4A is the prototype of a large family of proteins termed the DEAD box protein family, whose members share nine highly conserved amino acid regions. The functions of several of these conserved regions in eIF-4A have previously been assigned to ATP bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
235
5
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(261 citation statements)
references
References 61 publications
(51 reference statements)
20
235
5
1
Order By: Relevance
“…The RNA binding site of the helicase core is formed by both RecA-like domains, and binding involves contacts to motifs Ia, GG, and Ib in the N-terminal domain, and to motifs IV, QxxR, V, and VI in the C-terminal domain (Pause et al, 1993;Andersen et al, 2006;Bono et al, 2006;Sengoku et al, 2006;Nielsen et al, 2008;Collins et al, 2009;von Moeller et al, 2009) (Figures 1 and 3B). In all available structures, the N-terminal RecA-like domain binds the 39-region of the ssRNA substrate, and the C-terminal domain binds the 59-region.…”
Section: Rna Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…The RNA binding site of the helicase core is formed by both RecA-like domains, and binding involves contacts to motifs Ia, GG, and Ib in the N-terminal domain, and to motifs IV, QxxR, V, and VI in the C-terminal domain (Pause et al, 1993;Andersen et al, 2006;Bono et al, 2006;Sengoku et al, 2006;Nielsen et al, 2008;Collins et al, 2009;von Moeller et al, 2009) (Figures 1 and 3B). In all available structures, the N-terminal RecA-like domain binds the 39-region of the ssRNA substrate, and the C-terminal domain binds the 59-region.…”
Section: Rna Bindingmentioning
confidence: 99%
“…The binding sites can be independent, or coupled to each other via positive or negative cooperativity. Early experiments suggested sequential binding of ATP and RNA (Abramson et al, 1987;Pause et al, 1993). This conclusion resulted from the low RNA affinity of the helicase core in the absence of nucleotides, making RNA binding difficult to detect.…”
Section: Cooperativity Of Rna and Nucleotide Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the archetypal member of the DEAD box family of proteins, as the other members of this family are made up of core eIF4A-like domains flanked by N-and C-terminal extensions (5). eIF4A can unwind small duplex RNAs in vitro in conjunction with another factor, eIF4B (2,(6)(7)(8)(9). These and other observations have led to the proposal that the DEAD box proteins function as RNA helicases (2,6,8,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…It was demonstrated that the enzyme's affinity for RNA is modulated by the presence or absence of the γ-phosphate on the bound nucleotide. In addition, UV-induced RNA cross-linking experiments suggested that the presence or absence of the γ-phosphate also alters the conformation of the enzyme (9,14).To further explore ligand-induced conformational changes in eIF4A, limited proteolysis experiments were performed. These experiments provide evidence that distinct conformations of the enzyme are stabilized upon binding of the various combinations of substrates and products.…”
mentioning
confidence: 99%